Exploring the Dominance of Pull and Push Forces and Role of Geography towards Non-Farm Employment in Rural Tamil Nadu, India - Balaji, S.J., (Indian Journal of Extension Education, 2023)
The present study attempts to study the trend, distribution and determinants of nonfarm employment inrural Tamil Nadu using household level information provided in NSS-Employment Survey for the year2011-12. It employs Getis-Ord’s index of spatial correlation to study the employment distribution acrosssub-units of the state, and logistic regression to study the extent of influence of different pull and pushforces that attract/detract individuals engaging into nonfarm occupations. Results obtained show that thestate stands second among southern states employing around two-fifth of rural labor in nonfarm occupations,but labor absorption has slowed down since mid-1990s. Cross-sectional estimates show that nonfarmlabor shares are high in just one-sixth of all districts, and employment levels are low in 40 percent of thedistricts. low labor-share districts are at eastern region. To the other end, medium labor-share districts areprimarily located at western and northern region of the state. While southern districts show us a mixedpattern, districts with more than 60 percent nonfarm labor-share are scattered across the state. Maps ofGetis-Ord’s statistic show ‘cold spot’ cluster, providing evidence favoring spatial clustering in lowemployment regions. Among determinants, higher education and training stands matter the most in accessingto nonfarm occupations. Odds-ratio of logistic regression show that persons with a literacy level of graduationand above are 18 times more likely to access nonfarm jobs, whereas persons having vocational training arearound 4 times more likely to obtain nonfarm jobs. Interestingly, agricultural productivity, and farm-nonfarmwage ratio had no significant influence on accessing nonfarm jobs.